Pengaruh Upah Minimum Provinsi, Tingkat Pendidikan, dan Inflasi terhadap Penyerapan Tenaga Kerja di Provinsi Jawa Timur - Dhiarama, Rayhan Aflah; Hanifa, Nurul (Universitas Negeri Surabaya, 2024)
This study aims to determine the effect of provincial minimum wage, education level, and inflation on employment in East Java Province. This research uses a quantitative method using secondary data of the time series type in 1994 - 2023. The analysis technique uses multiple linear regression, with provincial minimum wage (x1), education level (x2), inflation (x3), and employment (Y), using the EViews 12 program. The results showed that the provincial minimum wage and education level variables had a positive and significant effect. Meanwhile, the inflation variable has a negative and insignificant effect. Meanwhile, the three variables simultaneously have a significant effect on labor absorption in East Java.